Imaging of odontogenic keratocyst of the jaw by panoramic radiography: a scoping review - Sri Sulastri; Ria Noerianingsih Firman; Lusi Epsilawati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: This review article is aimed to determine the imaging of odontogenic keratocyst of the jaw by panoramic radiography. Review: This research is a descriptive research using the scoping review method based on the Preferred Reporting Items for Systematic Review and Meta-analysis Scoping Review (PRISMA-Scr) which was conducted from February 2021 to April 2021. The search for literature related to the research topic was carried out through database of scientific articles on PMC NCBI, Pubmed NCBI, and Garuda as well as hand searching. The identified articles were screened by checking for duplicates, reading the titles and abstracts, and reading the entire articles. A total of 16 articles were included out of 161 articles in total. Conclusion: Imaging of odontogenic keratocyst of the jaw by panoramic radiography is most commonly found in the 1st and 2nd decades of life and in males, the lesions are unilocular or multilocular radiolucent and have an envelopmental shape in which the outline of the cyst surrounds the entire unerupted tooth. OKCs have well-defined with sclerotic or scalloped margins, most often occur in the posterior mandible and often associated with impacted 3rd molars, root resorption was a rare occurrence.